The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13012-016-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

The facilitators and barriers associated with implementation of a patient-centered medical home in VHA

Abstract: BackgroundThe patient-centered medical home (PCMH) is a team-based, comprehensive model of primary care. When effectively implemented, PCMH is associated with higher patient satisfaction, lower staff burnout, and lower hospitalization for ambulatory care-sensitive conditions. However, less is known about what factors contribute to (or hinder) PCMH implementation.We explored the associations of specific facilitators and barriers reported by primary care employees with a previously validated, clinic-level measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
5
31
0
Order By: Relevance
“…Transition processes described by PCMH interviewees aligned with the ten building blocks of highperforming primary care (8), particularly the foundational elements of engaged leadership, teambased care, and data-driven improvement. Consistent with international literature, our findings indicated that engaged leadership was imperative in driving PCMH transitions (6,7,42,43), and that team-based care was key to the model, requiring protected time for meetings to plan patient care (6,42,44). Conversely, lack of leadership and an absence of staff engagement, particularly among former PCMH interviewees, were cited as barriers to transition, as reported in other studies (7,45).…”
Section: Discussionsupporting
confidence: 80%
“…Transition processes described by PCMH interviewees aligned with the ten building blocks of highperforming primary care (8), particularly the foundational elements of engaged leadership, teambased care, and data-driven improvement. Consistent with international literature, our findings indicated that engaged leadership was imperative in driving PCMH transitions (6,7,42,43), and that team-based care was key to the model, requiring protected time for meetings to plan patient care (6,42,44). Conversely, lack of leadership and an absence of staff engagement, particularly among former PCMH interviewees, were cited as barriers to transition, as reported in other studies (7,45).…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with other studies our findings indicate that communication between all key project players is crucial for successful project implementation. Routine meetings are important to discuss practice change and to ensure whole team buy-in to the projects (12,45). Ongoing communication and relationship building with allied health services and LHD staff is important for service integration (46).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Effective care coordination, however, requires appropriate resources. 16 In the VA, inadequate staffing and time constraints are well-documented challenges of PACT implementation, [17][18][19][20] often associated with higher staff burnout 18 and lower scores on PACT implementation metrics. 19 Competing care delivery priorities and lack of communication from leadership about PACT performance metrics are additional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the VA, inadequate staffing and time constraints are well-documented challenges of PACT implementation, [17][18][19][20] often associated with higher staff burnout 18 and lower scores on PACT implementation metrics. 19 Competing care delivery priorities and lack of communication from leadership about PACT performance metrics are additional challenges. 19 Although the literature notes these challenges for PACT, less is known about how care coordination occurs in the context of the resource constraints and competing priorities of routine care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation